Geoheritage Values of the Northeastern Carpathians, Transcarpathia, Ukraine - Gönczy Sándor; Fodor Gyula; Oláh Natália; Nagy Tibor; Ésik Zsuzsanna; Szepesi János; Генці Шандор; Фодор Дюло; Олаг Наталія; Нодь Тіберій (Islamic Azad University - Isfahan Branch, 2020)
Abstract. Transcarpathia is politically the westernmost county of Ukraine but geographically is the northeastern part of the Carpathian–Pannonian Region. The aim of our present work is to provide a brief overview and greater publicity about the geoheritage values of Transcarpathia using 45 documented geosites (stratigraphic, volcanic, geomorphological, mineralogical, tectonic) of the Ukrainian State Geological Survey. Four objects are located in national parks or nature reserves. The other 41 sites are only recommended for protection. The applied classification scheme includes thematic (primary and additional interest) and functional categories (e.g. natural outcrops, quarries). The preliminary qualitative site assessment involved the determination of integrity, geological diversity, use limitations, current observation conditions, vulnerability, safety, and association with other value parameters. This review is a good methodological starting point for expanding the database and emphasizing the importance of abiotic nature. Conserving geodiversity requires protection for nationally or regionally important objects and what includes active management of sites.
Keywords: Transcarpathia; geodiversity; geosite; classification